1997
DOI: 10.1086/452308
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Education Impacts on Employment and Earnings in West Africa: Evidence from Guinea

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 0 publications
12
88
0
1
Order By: Relevance
“…This explains the fact that although a higher percentage of children may have been enrolled, most children in Nigeria are faced with delayed enrolment. Similar results have been found elsewhere (Glick and Sahn, 1997). More importantly, the test of differences between means shows that male participation in all child activity options is significantly different from female activity options except in the case of idling (see Appendix Table A1).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This explains the fact that although a higher percentage of children may have been enrolled, most children in Nigeria are faced with delayed enrolment. Similar results have been found elsewhere (Glick and Sahn, 1997). More importantly, the test of differences between means shows that male participation in all child activity options is significantly different from female activity options except in the case of idling (see Appendix Table A1).…”
Section: Resultssupporting
confidence: 85%
“…This is due partly to orientation and partly to experience. These results also re-echo the many studies showing that poverty and lack of schools drive children into economic activities (Basu, 1998;Glick and Sahn, 1997).…”
Section: Exclusive Child Labourerssupporting
confidence: 79%
See 1 more Smart Citation
“…Part of the differential of course, may be due to discrimination. For instance, Glick and Sahn (1997), using data from Guinea, found that 45 per cent of the earnings differential between males and females in self-employment was owing to discrimination against women. 7.…”
Section: Notesmentioning
confidence: 99%
“…In addition, average skill level of highly educated female workers is often higher than that of their male counterparts because, at any level of schooling, the threshold skill level at which women choose to participate in the labor market is higher. The coexistence of lower average wages and higher (or similar) returns to schooling for women has been observed in countries as varied as Indonesia (Behrman and Deolalikar 1995), Guinea (Glick and Sahn 1997) and Peru (King 1996). However, women are typically less educated than men in these countries due to gender earnings gaps and other social, cultural, and institutional factors which keep many women out of the labor force.…”
Section: Schooling and The Labor Marketmentioning
confidence: 99%